TO CHOSEN ASPECTS OF THE COMMON PLAYS BY KAREL HYNEK AND VRATISLAV EFFENBEGER - Strnadová, Karolina (Bohemica Olomucensia, 2022)
This study is focused on the common texts of Karel Hynek and Vratislav Effenberg, namely Jela tudy dáma (1950) and Poslední umře hlady (1952) which are commonly described as theatre plays. The main goal will introduce chosen aspects of both texts, mainly from politicaly-cultural point of view in these times, in context of official and surrealistic conception of theatre and also in other works by authors.
Keywords: Karel Hynek; Vratislav Effenberger; Jela tudy dáma; Poslední umře hlady; post-war surrealism; common texts; common plays; collective practice